STUDY OF IONIC LIQUID SURFACE MODIFIED SILICA MIXED MATRIX MEMBRANE FOR CARBON DIOXIDE SEPARATION - SHAFIE, SITI NUR ALWANI (2019)
Carbon dioxide (CO2) separation using mixed matrix membrane (MMM) has been reported to give superior separation performance. However, the benefit of MMM is limited by the adhesion problem between polymer/inorganic phase. Hence, study on modification of inorganic fillers in MMM has been widely conducted to overcome the problem.